The state of optics research in Colombia: a scientometric analysis (2022)
Although there is a perception in the community that the state of optics research in Colombia has reached a mature state with international recognition, to date, there is no study that supports this view quantitatively. We aimed to assess the state of optics research in Colombia based on international journal publications. Therefore, we determined scientometric indicators using the research articles published by authors with Colombian affiliation in journals indexed in the Scopus database belonging to the Atomic and Molecular Physics and Optics subject category. The research output has increased dramatically in the past two decades, with an average of 169 articles per year since 2016. Most of these articles are published in high-impact journals. A little over 10% of that research is in the top 10% most cited in the world. Over 25 higher education institutions contribute significantly to this research with many international and national collaborations. The normalized citation impact for Colombian optics research is 0.95, only five points below the world average, and ranked second in Latin America, only superseded by Chile (1.33). Our results show that optics research is an established research area in Colombia with high impact and many active groups from different institutions spread throughout the country.